Shark incidents in California 1950-2021; frequency and trends - Ugoretz, John; Hellmers, Elizabeth A.; Coates, Julia H. (Frontiers in Marine Science, 2022)
Many reports have categorized the frequency, circumstances, and causes for interactions between sharks and humans, often using the behaviorally inaccurate term “attack.” The California Department of Fish and Wildlife (Department) instead uses the term “incident,” defined as interactions where a shark touches a person, their board, or kayak, without provocation and with or without causing injury. We created a comprehensive database of California shark incidents by reviewing, verifying, and updating past records, and examined the frequency of confirmed incidents, updated reports with new information, and examined similarities and differences in incident circumstances. Two hundred and one incidents were verified in California waters between 1950 and 2021, with 107 causing injury and 15 resulting in fatalities. The vast majority (178) involved white sharks (Carcharodon carcharias). Contrary to past reports of white shark incidents being concentrated in a portion of northern California, incidents have occurred statewide, with some of the highest numbers in Southern California. While total reported incidents are increasing, the annual number of incidents resulting in injuries or fatalities remains low. Frequency of incidents was not found to be greater around the full moon, dawn, or dusk but was greater during summer and fall months, as expected.